2010
DOI: 10.1002/pi.2758
|View full text |Cite
|
Sign up to set email alerts
|

New design of actuator using shear piezoelectricity of a chiral polymer, and prototype device

Abstract: Chiral polymers have been known to exhibit small shear piezoelectricity for about fifty years. However, recently, we reported that poly(L-lactic acid) treated with supercritical carbon dioxide (sc-PLLA), which is a type of chiral polymer, exhibits much higher shear piezoelectricity than other chiral polymers. On the other hand, we found an important difference between motion due to shear piezoelectricity and that due to tensile piezoelectricity in piezoelectric materials through computer simulations. On the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Poly-L-lactic acid (PLLA), a biodegradable polymer used extensively in FDA-approved implants, has recently been found to exhibit piezoelectricity when appropriately processed (15)(16)(17). The material exhibits shear piezoelectricity due to electrical polarity present in the carbon-oxygen double-bond branching off from the polymer backbone chain (18,19). Although possessing a modest piezoelectric response (5-15 pC/N), PLLA has a low dielectric constant, which allows the material to perform the same energy-conversion efficacy as the common piezoelectric polymer PVDF (16,20).…”
Section: Significancementioning
confidence: 99%
“…Poly-L-lactic acid (PLLA), a biodegradable polymer used extensively in FDA-approved implants, has recently been found to exhibit piezoelectricity when appropriately processed (15)(16)(17). The material exhibits shear piezoelectricity due to electrical polarity present in the carbon-oxygen double-bond branching off from the polymer backbone chain (18,19). Although possessing a modest piezoelectric response (5-15 pC/N), PLLA has a low dielectric constant, which allows the material to perform the same energy-conversion efficacy as the common piezoelectric polymer PVDF (16,20).…”
Section: Significancementioning
confidence: 99%
“…Semi-crystalline PLLA does not require any additional poling treatment to induce piezoelectric effect. This has been attributed to the displacement of the C=O bond in PLLA in response to mechanical stress leading to generation of a net dipole moment and charge [145][146][147]. PLLA has been used to fabricate films, fibres and rods with piezoelectric behaviour [148][149][150][151] and it has been observed that crystallinity and polymer orientation play key role in piezoelectric characteristic [152].…”
Section: Pllamentioning
confidence: 99%
“…This is a well known buckling phenomenon observed in real fabrics and pipes conveying fluids, diamond-shaped patterns appear under the large axial compression of a cylindrical shell [12]. This phenomenon indicated that a large amount of stress was caused by the resonance phenomenon of the PLLA film roll [1,12,13]. Therefore, we considered that the likelihood of realizing a surface acoustic wave was increased.…”
Section: Resonance Phenomena Of Plla Film Roll Transducermentioning
confidence: 96%